Lemmatisering og tilgangsstruktur Refleksjoner på bakgrunn av Íslenskt orðanet - Jónsson, Jón Hilmar (Nordiske Studier i Leksikografi, 2007)
This article discusses how an electronic presentation of a dictionary description provides the means of a wider, but simultaneously more specific, lemmatisation than previously practised in printed dictionaries. This especially applies to multiword lemmas. At the same time users are offered a more varied access to the lexicographic information contained within the dictionary. Here, these possibilities are being evaluated with respect to an ongoing Icelandic lexicographic project named Íslenskt orðanet (Icelandic Wordnet). The material of the wordnet is mainly drawn from the contents of dictionaries of Icelandic phrases, and the data is used to identify semantic relations within the Icelandic vocabulary, for single words as well as for phrases. In the lemmatisation of the material the primary consideration is semantic disambiguation. Furthermore, multiword units, particularly various verbal phrases, are given a lemma status equal to that of single words. That way, the dictionary description is made accessible from many different directions, both towards particular semantic fields and related lemmas within those fields, and towards formally related lemmas.